Enhanced diffraction by a rectangular grating made of a negative phase-velocity (or negative index) material - Depine, Ricardo Angel (2005)
The diffraction of electromagnetic plane waves by a rectangular grating formed by discrete steps in the interface of a homogeneous, isotropic, linear, negative phase-velocity (negative index) material with free space is studied using the semi-analytic C method. When a nonspecular diffracted order is of the propagating type, coupling to that order is significantly larger for a negative index material than for a conventional material. The computed coupling strengths reported here are in agreement with recent experiments, and illustrate the role of evanescent fields localized at the grating interface in producing this enhanced coupling. © 2005 Published by Elsevier B.V.